Water content in pear tree tissues during the dormancy period under mild winter conditions - Marafon, Anderson Carlos; Herter, Flavio Gilberto; Hawerroth, Fernando José (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the water content (WC) in different tissues of the Kieffer (Pyrus communis) and Housui (Pyrus pyrifolia) pear cultivars during dormancy, under mild winter conditions. Plants from to the experimental orchard of Embrapa Clima Temperado, Pelotas, RS, Brazil, were evaluated. A completely randomized block design, in a 3x4x5 factorial arrangement, consisting of three tissues (bud, bark and wood), four portions of branches (terminal, median, axial and spurs) and five sampling dates in 2005 (7/1, 8/3, 9/6, 9/23 and 10/13), distributed in split‑plots, with three replicates, was used. There was a WC increase in the wood of the Kieffer cultivar until the middle of the dormancy period and a subsequent decrease after this phase, which could be attributed to the increase in WC observed in buds after the satisfaction of chilling requirement and dormancy. In the cultivar Housui, unsatisfactory chilling requirement, associated with the occurrence of high temperatures during the winter, reflected in the reduction of WC and in bud dehydration during dormancy. Water dynamics in pear tree tissues is directly influenced by cold accumulation during dormancy period and depends on the cold requirement of each cultivar.